Lexical Productive Competency as a Predictor of Academic Performance - Gonzalo Zapico, Martín (2018)
Academic performance at the high level, specifically the ability to predict it, is an issue of enormous profusion in terms of both theory and practice. There is an agreement among researchers that in how difficult it is as part of the difficulty to establish predictors, three of them have a moderate but inconclusive correlation degree: past performance in high-school level, motivation in all of its nuances, and critical judgment. The hypothesis of this paper is that the productive lexical knowledge of a subject, which can be evaluated in terms of synonymy, is a factor that will determine the academic performance. For this purpose quantitative comparison (descriptive and correlational statistics) of the performance obtained by four groups of students of professorships Language, English, Primary education and History in their respective introductory courses of the Instituto de Formación Docente Continua (IFDC located in San Luis, Argentina), whom previously had been administered a test of synonyms, was performed. The results suggest that productive lexical knowledge, assessed in terms of synonymy, is a factor that predicts academic performance, and therefore it is pertinent to consider implementing it aimed at promoting this competence in the introductory courses of top level education programs.